Errata for Three Papers (2004-05) on Fixed-Priority Scheduling with Self-Suspensions - Bletsas, Konstantinos (2019)
The purpose of this article is to (i) highlight the flaws in three previously published works [Audsley, 2004a; Audsley, 2004b; Bletsas, 2005] on the worst-case response time analysis for tasks with self-suspensions and (ii) provide straightforward fixes for those flaws, hence rendering the analysis safe.